APLIKASI EASY TERNAKFRONT END MITRA PETERNAK - Kesuma Adistana, Yenni (Journal Information Technology Trends (JITRENDS), 2023)
Goat farming has great potential in South Kalimantan. The need for goat meat in South Kalimantan is now very high, especially during religious activities in the form of aqiqah and sacrifice. When compared with the selling price of goats outside the region, the price of goats in South Kalimantan is quite high, the cause is the limited population of goats in South Kalimantan. This limited population is caused by several things, one of which is that many farmers are constrained by capital in developing their farms, the solution that can be done is an application called Easy Livestock that can bring together farmers and the community. The stages of developing this application are starting from designing Entity Relationship Diagrams, Data Flow Diagrams and Flowcharts, developing using the Flutter Framework, and MySQL database, also in development based on a prototype model. This application called Easy Ternak can provide information on goat menus, partners and investors. According to the test, this application also shows the success rate when run, so that this application will run smoothly, from deleting, deleting, and viewing data.